2019
DOI: 10.1021/acsearthspacechem.9b00065
|View full text |Cite
|
Sign up to set email alerts
|

Complex Organic Molecules in Star-Forming Regions of the Magellanic Clouds

Abstract: The Large and Small Magellanic Clouds (LMC and SMC), gas-rich dwarf companions of the Milky Way, are the nearest laboratories for detailed studies on the formation and survival of complex organic molecules (COMs) under metal poor conditions. To date, only methanol, methyl formate, and dimethyl ether have been detected in these galaxies -all three toward two hot cores in the N113 star-forming region in the LMC, the only extragalactic sources exhibiting complex hot core chemistry. We describe a small and diverse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 166 publications
(418 reference statements)
0
17
0
Order By: Relevance
“…Prior to the present study, COMs with more than six atoms had only been detected toward two hot cores in the LMC: A1 and B3 in the star-forming region N 113 (N 113 A1 and N 113 B3;Sewiło et al 2018Sewiło et al , 2019. Sewiło et al (2018) reported the detection of methyl formate (HCOOCH 3 ) and dimethyl ether (CH 3 OCH 3 ), together with their likely parent species CH 3 OH, with fractional abundances with respect to H 2 (corrected for a reduced metallicity in the LMC with respect to the Milky Way) at the lower end, but within the range measured toward Galactic hot cores.…”
Section: Hot Molecular Cores In the Lmcmentioning
confidence: 78%
See 1 more Smart Citation
“…Prior to the present study, COMs with more than six atoms had only been detected toward two hot cores in the LMC: A1 and B3 in the star-forming region N 113 (N 113 A1 and N 113 B3;Sewiło et al 2018Sewiło et al , 2019. Sewiło et al (2018) reported the detection of methyl formate (HCOOCH 3 ) and dimethyl ether (CH 3 OCH 3 ), together with their likely parent species CH 3 OH, with fractional abundances with respect to H 2 (corrected for a reduced metallicity in the LMC with respect to the Milky Way) at the lower end, but within the range measured toward Galactic hot cores.…”
Section: Hot Molecular Cores In the Lmcmentioning
confidence: 78%
“…A typical Galactic hot core has a very rich spectrum at submm wavelengths including lines from many complex organics -the products of interstellar grain-surface chemistry or postdesorption gas chemistry (e.g., Herbst & van Dishoeck 2009;Oberg 2016;Jørgensen et al 2020). Methanol has also been detected toward a handful of other locations in the LMC, but outside hot cores ("cold methanol"; see e.g., Sewiło et al 2019).…”
Section: Hot Molecular Cores In the Lmcmentioning
confidence: 99%
“…While this model has been applied to meteoritic amino acids, we note that other organic molecules have been found in meteorites [e.g., [107][108][109][110][111][112] and comets [113], and the search for extraterrestrial organic molecules remains an active field in observational astronomy [e.g., [114][115][116][117] and planetary science [e.g., [118][119][120][121][122]. However, in addition to chiral amino acids, other chiral organic molecules have been found in meteorites with non-zero enantiomeric excesses [123,124] as well as isotopic ratios which differ from terrestrial values [124].…”
Section: Discussionmentioning
confidence: 99%
“…N113, located in the central part of the LMC, contains the most intense H 2 O maser of the Magellanic Clouds (Ellingsen et al 2010), which indicates active star formation activity at an early stage. A large number of molecular transitions have been reported in N113 (e.g., Chin et al 1996Chin et al , 1997Heikkilä et al 1998;Wang et al 2009;Paron et al 2014;Nishimura et al 2016;Tang et al 2017b;Sewiło et al 2018Sewiło et al , 2019, while interferometric data from HCN, HCO + , HNC, CH 3 OH, and 1.3 mm continuum (Wong et al 2006;Seale et al 2012;Sewiło et al 2018Sewiło et al , 2019 reveal a filamentary structure elongated roughly North-South with a length of ∼6 pc, including a few dense clumps with radius ∼0.5 pc. N159W, located at the southwestern tip of 30 Doradus, one of the most intense star-forming regions in the LMC, contains a large number of O-and B-type stars, embedded young stellar objects (YSOs), and ultracompact H II regions (e.g., Jones et al 2005;Fariña et al 2009;Chen et al 2010;Carlson et al 2012).…”
Section: Targetsmentioning
confidence: 99%